John Henry and his people : the historical origin and lore of America's great folk ballad - Garst, John F. (McFarland & Company, 2022)
"The song "John Henry," often dubbed America's greatest folk ballad, is about an African-American steel driver who raced and beat a steam drill, dying "with his hammer in his hand" from the effort. Most singers and historians believe John Henry was a real person, not a fictitious one, and that his story took place in Dunnavant, Alabama. The author's reconstruction, based on contemporaneous evidence and subsequent research, uncovers a fascinating story that supports the Dunnavant location and provides new insights for both general readers and folklorists. Beyond John Henry, readers will discover the lives, stories and work of his people: Black and white singers; his "captain," contractor Frederick Dabney; C.C. Spencer, the most credible eyewitness; John Henry's wife, the blind singer W.T. Blankenship, who printed the first broadside of the ballad; and later scholars who studied John Henry. Wide-ranging in its scope, this book includes analyses of the song's numerous iterations, several previously unpublished illustrations and a foreword by folklorist Art Rosenbaum"--